Social media as a marketing tool: The example of five-star hotels in Gdansk - Pyrka, Julia (Who needs tourism?, 2024)
The aim is to present, discuss and compare methods of managing social media profiles (Facebook and Instagram). Five-star hotels in Gdańsk were selected for the research and prove that the basis for managing an effective social media profile is consistency, proper promotion and clarity of publication, and that these have an impact on the results achieved. Data collected from hotel profiles on social media were collated, compared and analyzed. Based on the collected information, the engagement rate was calculated, allowing for an objective assessment of how the content published by the profiles is perceived. The aspects discussed in the article were intended to show what mistakes hotels make in managing their social media profiles and how they can mitigate them.